PENGARUH TRANSFER PRICING TERHADAP PERENCANAAN PAJAK BAGI PERUSAHAAN MULTINASIONAL - Chandra, Tri Martha (Jurnal Akuntansi AKUNESA, 2014)
Transfer pricing is a classical issue in international transaction. Transfer pricing could be conducted among others with taxes motivation, in which the main objective is to transfer tax burden from the higher rated country to the lower rate jurisdiction. The key to a successful practise of transfer pricing from tax standpoint is the existence of related parties transaction. To regulate the transfer pricing practice, the regulations govern the authority to realocate transfer price among divisions that have related parties transaction.Keyword: Transfer pricing, Tax